IN NAVOI'S“KHAMSA” WOMEN IMAGE (American Journal of Pedagogical and Educational Research, 2023)
This in the article ghazal of property sultan mirAlisher Navoi to the pen belonging to `` Khamsa '' women of the image great examples , female qualities , thinker by to them given beautiful allusions , definitions , as well as Navoi 's a woman to its value relationship described